2013
DOI: 10.1542/peds.2013-1614
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Vs Broad-spectrum Antimicrobial Therapy for Children Hospitalized With Pneumonia

Abstract: BACKGROUND: The 2011 Pediatric Infectious Diseases Society/Infectious Diseases Society of America community-acquired pneumonia (CAP) guideline recommends narrow-spectrum antimicrobial therapy for most children hospitalized with CAP. However, few studies have assessed the effectiveness of this strategy. METHODS: Using data from 43 children’s hospitals, we conducted a retrospective cohort study to compare outcomes and resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 30 publications
4
68
0
1
Order By: Relevance
“…2018; 6(1):e34474. 5 cillin/penicillin vs. ceftriaxone/cefotaxime) found no appreciable difference in a length of hospital stay, admission to the intensive care unit or readmission between the two groups, however, the cost of treatment in those receiving broad spectrum antibiotics was higher (17). A qualitative study on the use of antimicrobials in the medical department of a teaching hospital reported needless administration of antibiotics in about 23% of the cases while overprescribing of broad-spectrum antibiotics in situations, where a narrow-spectrum antimicrobial would have been sufficient was identified as the most common prescribing error (23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…2018; 6(1):e34474. 5 cillin/penicillin vs. ceftriaxone/cefotaxime) found no appreciable difference in a length of hospital stay, admission to the intensive care unit or readmission between the two groups, however, the cost of treatment in those receiving broad spectrum antibiotics was higher (17). A qualitative study on the use of antimicrobials in the medical department of a teaching hospital reported needless administration of antibiotics in about 23% of the cases while overprescribing of broad-spectrum antibiotics in situations, where a narrow-spectrum antimicrobial would have been sufficient was identified as the most common prescribing error (23).…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, ceftriaxone or other broad spectrum cephalosporins have been cited as the most frequently used antibiotics in several other studies (15)(16)(17)(18). Extensive use of the third generation cephalosporins has led to the emergence of extended beta-lactamase-(ESBL) producing 4 Arch Pediatr Infect Dis.…”
Section: Discussionmentioning
confidence: 99%
“…29, 30 We included only potential confounders that were highly likely to be determined concurrently with or before the decision to administer glucocorticoids, to avoid inadvertently including mediators or colliders in the model. Potential confounders included demographic characteristics, such as age, sex, race (white, black, Asian, or other), and insurance status (public, private, or other).…”
Section: Covariatesmentioning
confidence: 99%
“…No patient-level clinical data exists in the database, but this administrative database has been used previously for comparative effectiveness research. 10,11 …”
Section: Data Source and Designmentioning
confidence: 99%